ISLAM DAN GLOBALISASI - Ahmad Fauzan Azzim; Dais Siti Robiah Latifah; Asep Abdul Muhyi (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
In this era of globalization, all information related to current events is worthy of research. The impact on the social system, this situation must be addressed wisely. Islam is a universal religion. Therefore, Islam has a big influence on social change (globalization). This change (globalization) certainly has positive and negative impacts. However, Muslims must be intelligent and wise to move towards globalization. The aim of this research is to address the position of Islam which has reached the global stage through a qualitative descriptive approach. The existence of globalization in the Islamic world has become the focus of attention being discussed to date. The reason for the dispute is fundamental, so how should a Muslim respond to it? Can we as Muslims follow a globalization model that is not in accordance with Islamic principles, if so, how? Those are some of the things we will discuss this time, God willing.